Parametric analysis of ball milling condition on thermoelectric performance of Bi0.6FeCo3Sb12 skutterudite - Raihan, Ovik; Said, Suhana Mohd; Sabri, Mohd Faizul Mohd; Rozali, Shaifulazuar; Long, Bui Duc; Kimura, Kaoru; Tobita, Kazuki; Fitriani, -; Salleh, Faiz; Ali Bashir, Mohamed Bashir (IOP Publishing, 2018)
The FeCo 3 Sb 12 skutterudite crystal was doped with Bi to act as a filler material for the Bi 0.6 FeCo 3 Sb 12 formulation. It was prepared by ball milling and spark plasma sintering. The microstructure and thermoelectric performance of the bulk skutterudite was evaluated as function of its mechanical alloying process, i.e. ball milling. Rietveld analysis of its XRD spectra indicated that The Bi doping on the Co 4 Sb 12 based skutterudite succeeded in partially filling the voids of the skutterudite, whilst the Fe doping partially substituted the Co sites in the lattice. This serves to simultaneously increase the electrical conductivity whilst reducing the thermal conductivity of the resulting skutterudite. The ball milling times was correlated to the resulting microstructure, and ultimately, its thermoelectric performance. It was found that the moderate milling times (at 15 h) resulted in the best electrical conductivity, given the homogenous distribution of particles. A Maximum ZT value was observed 0.18 for 10 h ball milled sample at 673 K, whilst almost the same value was achieved for the 15 h ball milled sample, i.e. ZT = 0.17 at 673 K. Beyond this milling time, agglomeration of particles after ball milling caused degradation in the overall thermoelectric performance. Thus, this paper presents a strategy optimize the mechanical alloying process parameters to provide improved thermoelectric performance.